Pengaruh Risiko Kredit dan Risiko Likuiditas terhadap Profitabilitas Perusahaan Perbankan yang terdaftar di BEI - Nurasyidputri, Aqida (Journal of Trends Economics and Accounting Research, 2025)
This research aims to determine the effect of credit risk (NPL) and liquidity risk (LDR) on the profitability of banking companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period. The population in this research is all banking companies registered on the IDX. The sampling method used a purposive sampling method, a sample of 11 banking companies was obtained. The research method used a descriptive quantitative method. The analysis method uses multiple regression analysis with classical assumption tests. The research results show that credit risk partially has a significant effect on profitability. This is proven by the calculated - t value < - t table and the significance value is smaller than 0.05. The research results show that partial liquidity risk has no effect on the profitability value. This is proven by the t count < t table and the significance value is greater than 0.05. The research results show that simultaneously credit risk and liquidity risk have a positive effect on profitability. This is proven by obtaining a calculated F value of 15.75 and an F table of 3.175, meaning calculated F > F table and with a significance value of 0.000. The resulting significance value is smaller than 0.05 (p < 0.05).